2017
DOI: 10.1016/j.nucmedbio.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeling and biological characterization of TPGS-based nanomicelles by means of small animal imaging

Abstract: This work demonstrated that TPGS based nanomicelles are susceptible to be radiolabeled with Tc thus they can be used to perform imaging studies in animal models. Moreover radiolabeling of these delivery nano systems reveals their possibility to be used as diagnostic agents in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Tesan et al reported that 99m Tc radiolabeled TPGS micelles and displayed excellent radiostability in vivo. 47 Hence, the radiolabeling of HA-CHEMS-Cur-TPGS NPs could be explained by the complexation of 99m Tc and carboxyl group or two close ester groups. The successful radiolabeling of 99m Tc was found to provide an opportunity for radionuclide 188 Re to be used as internal radionuclide therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Tesan et al reported that 99m Tc radiolabeled TPGS micelles and displayed excellent radiostability in vivo. 47 Hence, the radiolabeling of HA-CHEMS-Cur-TPGS NPs could be explained by the complexation of 99m Tc and carboxyl group or two close ester groups. The successful radiolabeling of 99m Tc was found to provide an opportunity for radionuclide 188 Re to be used as internal radionuclide therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As with other NP types, several studies have reported the radiolabelling of polymeric micelles with 99m Tc using the direct labelling method. [390][391][392][393][394][395][396][397][398] Once again, this was shown to be a robust technique; with reported RCYs generally being 495% under optimised conditions and serum stability ca. 98% after 24 h. [395][396][397] The radioiodination of polymeric micelles has also been reported.…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 97%
“…One might hypothesize that a poor bioavailability of TPGS-1000 in cardiac tissue could explain this lack of effect. Although TPGS-1000 is well tolerated in vivo and has a good bioavailability, previous studies suggested that it has a weak tropism for cardiac tissue [31]. [33], and thus care must be taken for its use in drug delivery.…”
Section: Discussionmentioning
confidence: 99%